The impact of low plasma atherosclerosis index on hemorrhagic transformation after endovascular treatment of large artery atherosclerotic stroke - Hu, Jianqiang; Cheng, Mingqing; Ma, Shuyu; Zhang, Jiawei; Miao, Xin; Liu, Tingting; Zheng, Kefangyuan; Fang, Yalan; Zhang, Jin (Frontiers in Neurology, 2025)
ObjectiveThe plasma Atherosclerosis Index (AIP) reflects lipid metabolism, but its relationship with hemorrhagic transformation (HT) after endovascular treatment (EVT) in large artery atherosclerotic stroke (LAA) is unclear. This study aims to assess AIP’s potential in predicting HT occurrence.MethodsThis retrospective study analyzed 467 LAA patients. The patients were grouped based on infarct volume (small, moderate, and large). Univariate and multivariate logistic regression models evaluated the relationship between AIP levels and HT risk. Additionally, we analyzed hemorrhagic infarction (HI), parenchymal hemorrhage (PH) and symptomatic hemorrhagic transformation (sHT) to evaluate the relationship between AIP and the risk of them.ResultsAmong the 467 patients, 199 experienced HT after EVT. After adjusting for confounders in the multivariate logistic regression model, lower AIP (OR = 0.20, p = 0.001) was significantly associated with an increased risk of HT. Subgroup analysis revealed that in the small infarct volume group, lower AIP (OR = 0.11, p = 0.012) was significantly associated with the risk of HT. AIP was also significantly associated with the risk of HI (OR = 0.12, p = 0.003) and sHT (OR = 0.11, p = 0.002) in HT.ConclusionLower AIP levels are an independent risk factor for HT after EVT in LAA patients, especially in the small infarct volume group. Moreover, AIP is associated with HI and sHT.